Development of Doratoon Animation Media on the Material of Faith in the Angels of Allah to Improve the Abillty to Memorize Daily Prayers - Yunisa Azahra; Ayunda Nur Arifah; Imam Tabroni; Deng Jiao; Lie Jie (Journal Emerging Technologies in Education, 2023)
Background. This research aims to create a Doratoon application-based learning media product to train children's understanding of faith in God's angels using the Doratoon application. This research uses a type of development research known as Research & Development (R&D Purpose. The research process begins with a preliminary study to see the problems that occur, the potential for development. Method. determining the literature review that is relevant to the problems that occur to plan the manufacture of initial product design, initial product field trials, product revision I, main field trials, product revision II. Results. , operational field trials, final product revision and dissemination and implementation of product application. Conclusion. The results of the research on the use of the Doratoon Application developed in this study with a series of steps and trial stages can be said to be successful in training children's understanding of faith in the angels of God because there is an increase in scores at each stage of the trial carried out